2001
DOI: 10.1046/j.1461-9563.2001.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod diversity of exotic vs. native Robinia species in northern Arizona

Abstract: Summary1 Arthropods were collected on native locust, Robinia neomexicana A. Gray, and exotic Robinia pseudoacacia L. in northern Arizona over a 2‐year period to determine the number of arthropod species and number of individuals present.2 More arthropod species were found on the native (251) than on the exotic Robinia (174).3 Greater species diversity was likewise found on the native than the exotic. The five most numerous insects collected each year accounted for 81% to 91% of the total number collected on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…Despite the forecasts performed by previous studies (Zobel et al, 1987;Dalin and Bjö rkman, 2006), our inventory showed that nowadays exotic conifers in France are as colonised by indigenous bark beetles as native ones. However and as pointed out by (Degomez and Wagner, 2001), from a purely economic perspective, the total number of pest species on an exotic tree may be less relevant to damage than the impact of a particular pest. Among the 13 bark beetle species collected on the exotic tree species that we considered, 12 were significant conifer pests in Europe, such as P. chalcographus or I. typographus which exhibited a high ability to colonise all exotic Pinaceae species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the forecasts performed by previous studies (Zobel et al, 1987;Dalin and Bjö rkman, 2006), our inventory showed that nowadays exotic conifers in France are as colonised by indigenous bark beetles as native ones. However and as pointed out by (Degomez and Wagner, 2001), from a purely economic perspective, the total number of pest species on an exotic tree may be less relevant to damage than the impact of a particular pest. Among the 13 bark beetle species collected on the exotic tree species that we considered, 12 were significant conifer pests in Europe, such as P. chalcographus or I. typographus which exhibited a high ability to colonise all exotic Pinaceae species.…”
Section: Discussionmentioning
confidence: 99%
“…The larger the resources represented by introduced plants are, the more rapidly the insects can adapt to these new hosts (Strong, 1974;Strong et al, 1977;Degomez and Wagner, 2001). Together with bark thickness similarities with P. sylvestris, this could also explain why P. menziesii, the most planted conifer species in France (Riou-Nivert, 1996), exhibited high bark beetle species richness although it has no congener in Europe.…”
Section: Other Host-related Influencing Factorsmentioning
confidence: 99%
“…However, the degree of depletion is dependent on the presence or absence of congeneric species as well as on the chemical components of the plants, and a trend to more-generalized species on non-native plants has been observed (Degomez and Wagner, 2001;Brändle et al, 2008;Bertheau et al, 2009;Goßner et al, 2009). Of the four non-native tree genera, only on Robinia were much fewer scolytids recorded than expected from the regression of species number versus resource availability, although Robinia was introduced to Europe around 1602 (Mayer, 1977).…”
Section: Scolytids On Non-native Hostsmentioning
confidence: 99%
“…R. pseudoacacia was introduced for afforestation from its native range in south-eastern North America to other areas of North America and in temperate South America, northern and southern Africa, temperate Asia, Europe, Australia and New Zealand (Weber, 2003;Sitzia et al, 2012), where it has undergone rapid expansion and became in many places an invasive plant (IUCN; Cierjacks et al, 2013). It is one of the most widely-planted tree species in the world after several Eucalyptus and Poplar species (Boring and Swank, 1984;Degomez and Wagner, 2001) and it is cultivated worldwide because of the high-quality timber properties, because of its ability to grow under different soil and climatic conditions and its tolerance to drought and erosion (Böhm et al, 2011;Cierjacks et al, 2013). Natural reproduction of the black locust is primarily vegetative through root suckering and stump http://dx.doi.org/10.1016/j.foreco.2016.05.025 0378-1127/Ó 2016 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%